2010
DOI: 10.1111/j.1750-3841.2010.01739.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluation of Microstructural Changes and their Relations with Some Physical Characteristics of Food during Drying

Abstract: Either the normalized changes of the fractal dimension of microstructural images of a sample or the normalized changes of the sample average cell diameter can be a useful tool in monitoring the drying process by 1st assessing the product volumetric shrinkage, which can be assessed easily on-line and on a real-time basis by such techniques as image analysis, and then relating the obtained results through microstructural changes to other apparent physical changes, including the product texture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 18 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…This phenomenon has the potential to be further investigated in detail during future investigations. 3-D model predictions for carrot cells during drying have been compared with experimental findings on real carrot microstructure 35,59 (see Fig. 14).…”
Section: Quantifying the Morphological Behaviour Of The Models Througmentioning
confidence: 99%
“…This phenomenon has the potential to be further investigated in detail during future investigations. 3-D model predictions for carrot cells during drying have been compared with experimental findings on real carrot microstructure 35,59 (see Fig. 14).…”
Section: Quantifying the Morphological Behaviour Of The Models Througmentioning
confidence: 99%
“…When the mechanical stress exceeded the critical value, the collapse in dehydrated cells occurred. Sansiribhan et al [47] also found that the cell diameter decreases rapidly when the moisture content was less than about 0.1. Moreover, the loss of components in cell structure can also reduce the firmness of cell structure.…”
Section: Impacts Of Moisture Transfer On Microstructurementioning
confidence: 92%
“…Therefore, at the same zone of the sample (close to the center of the slice), the degree of penetration of the solution was lower for samples subjected to the DC70-2 condition than for samples subjected to the DC60-2 condition. This behavior may result from cellular collapse of the tissue, which has been reported during drying at high temperatures (Ramos et al 2004;Sansiribhan et al 2010). Collapse of the tissue prevents the generation of a homogeneous impregnation profile.…”
Section: Description Of Experimental Diffusion Profiles By Image Analmentioning
confidence: 97%